Kajian Redesign Struktur Gedung 5 Lantai Balai Pengobatan Universitas Siliwangi - Al Huseiny, Mohammad Syarif; Nursani, Rosi (Akselerasi : Jurnal Ilmiah Teknik Sipil, 2024)
The Siliwangi University Medical Center is a simple building consisting of 1 floor which requires redesign to improve the quality of health services at Siliwangi University. High-rise buildings require precise and thorough structural calculations. The building must be able to withstand axial forces and lateral loads including earthquake loads. The results of the calculation of structural strength are made as optimal as possible so that it becomes a strong and stable building that can provide security and comfort for its users. Based on these problems, it is necessary to conduct research studies on the structure of the Siliwangi University Medical Center building. The dimensions of the structural components are determined by preliminary design first, then the building structure is analyzed using the SAP 2000 v.22.0.0 program. The next step is design control to determine whether the structural design meets the planning requirements and safety factor regulations or not. The results showed that the reinforced concrete structure in the Siliwangi University Medical Center building had strength control which qualify to the requirements, so the Siliwangi University Medical Center Building could be a safe and comfortable infrastructure that the health service process could run smoothly.